Automatický systém pro příjem a zpracování družicových meteorologických snímků - Baran, Ondřej; Vyskočil, Pavel; Kasal, Miroslav; Baran, Václav (International Society for Science and Engineering, o.s., 2010)
Článek je věnován problematice příjmu a zpracování meteorologických dat získávaných z meteorologických družic. Jedná se o družice NOAA na polárních drahách provozované americkou organizací National Oceanic and Atmosphere Administration, u kterých se využívá analogové služby APT. Dále jsou zpracovávána digitální data geostacionárních družic Meteosat evropské organizace EUMETSAT.

The paper is focused on the reception and the processing of meteorological data obtained from meteorological satellites. Firstly, polar satellites NOAA, that are operated by the American organization National Oceanic and Atmosphere Administration, are spoken. Here, the analog service APT is utilized. Consequently, digital data from geostationary satellites Meteosat are processed. These satellites are operated by the European organization EUMETSAT.
Automatic system for reception and processing of satellite meteorological images
Keywords: Meteorologická družice; polární družice; geostacionární družice; meteorologické snímky; Meteorological satellite; polar satellite; NOAA; geostationary satellite; meteorological images; Meteosat; NOAA; METEOSAT; MSG.; MSG.